2021
DOI: 10.1186/s13071-021-04685-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fluralaner as a treatment in controlling Dermanyssus gallinae infestation on commercial layer farms and the potential for resulting benefits of improved bird welfare and productivity

Abstract: Background Poultry red mite (PRM) (Dermanyssus gallinae) infestations are a cause of anaemia, impaired productivity and stress-related behaviours linked to reduced hen welfare. A study investigated the potential health, welfare and productivity benefits following fluralaner treatment to eliminate PRM from infested hens. Methods A PRM-infested layer house was selected on a free-range farm (5400 hens) and an aviary farm (42,400 hens). Fluralaner (Exz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…To the authors’ knowledge, this is the first time that the effect of the PRM load on the plumage condition has been demonstrated in a longitudinal study design over the laying period. Recently, Petersen et al [ 13 ] and Temple et al [ 12 ], using direct behavioral observations, found a reduction in SFP with treatment-induced decrease in the PRM load in laying flocks treated with fluralaner, which is an isoxazoline to be administered via the drinking water for mite control. Temple et al [ 12 ] discussed the concomitant reduction in pain and frustration with the reduction in the PRM load in the flocks as relevant to their findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the authors’ knowledge, this is the first time that the effect of the PRM load on the plumage condition has been demonstrated in a longitudinal study design over the laying period. Recently, Petersen et al [ 13 ] and Temple et al [ 12 ], using direct behavioral observations, found a reduction in SFP with treatment-induced decrease in the PRM load in laying flocks treated with fluralaner, which is an isoxazoline to be administered via the drinking water for mite control. Temple et al [ 12 ] discussed the concomitant reduction in pain and frustration with the reduction in the PRM load in the flocks as relevant to their findings.…”
Section: Discussionmentioning
confidence: 99%
“…PRM infestation is accompanied by a reduction of laying performance and egg weights [ 12 ]. Due to the particular lifestyle of PRMs, with includes long stays away from their hosts in hiding places that are difficult to access [ 1 ], alternative strategies, such as the heat treatment of barns [ 32 ] or medical treatment of hens via drinking water [ 12 , 13 ], are becoming increasingly important. Decru et al [ 33 ] recommended an integrated pest management approach to PRM control, with the prevention of introduction and the monitoring of parasite loads as key approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The poultry production system considers infestation by Dermanyssus gallinae , commonly referred to as the poultry red mite (PRM), to be a matter of concern because of its deleterious impact on both productivity and welfare of the animals [ 1 , 2 ]. In addition, in highly infested environments, poultry workers may also be at risk of infestation by PRMs, with clinical conditions varying from itching, dermatitis and erythematous rashes to papules, urticarial plaques and erythema [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%